The dual impact: physiological and psychological effects of rapid weight loss in wrestling - Sariakçali, B.; Sahin, F. N.; Basoglu, B.; Ceylan, L.; Güler, Ö.; Yamak, B.; Arikan, G.; Acar, G. C.; Sekban, G.; Durmusoglu, M. V.; Polat, S. Ç.; Küçük, H. (Frontiers in Psychology, 2024)
Introduction: Athletes competing in weight-class sports often seek to gain an advantage by competing at lower weights. Athletes competing in weight-class sports often seek to gain an advantage by competing at lower weights. To achieve this, they aim to lose weight during the competition period, leading to various physiological and psychological changes. This study aimed to investigate the biochemical, hormonal, and psychological effects of weight reduction in elite wrestlers during the competition phase.